2017
DOI: 10.3389/fpls.2017.00093
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Host-Pathogen Interactions with Expression Profiling of NILs Carrying Rice-Blast Resistance Pi9 Gene

Abstract: Magnaporthe oryzae infection causes rice blast, a destructive disease that is responsible for considerable decrease in rice yield. Development of resistant varieties via introgressing resistance genes with marker-assisted breeding can eliminate pesticide use and minimize crop losses. Here, resistant near-isogenic line (NIL) of Pusa Basmati-1(PB1) carrying broad spectrum rice blast resistance gene Pi9 was used to investigate Pi9-mediated resistance response. Infected and uninfected resistant NIL and susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 122 publications
2
51
0
Order By: Relevance
“…WRKY transcription factors were again and again observed to be implicated in the rice resistance to Mor [8,68,69]. In our analysis, WRKY proteins (IPR003657) were the most frequently activated transcription factors by Mor (Table S26).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…WRKY transcription factors were again and again observed to be implicated in the rice resistance to Mor [8,68,69]. In our analysis, WRKY proteins (IPR003657) were the most frequently activated transcription factors by Mor (Table S26).…”
Section: Discussionsupporting
confidence: 60%
“…A number of researches reported the expression profiles of rice defense response genes [9,67]. For example, chitinase activities were detected to play roles in rice resistance to Mor [68,69]. Our results show that the expected defense enzymes were the most frequent products of the regulated genes by Xoo and Mor (Fig.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…9E ). The induction of chitinase can help to strengthen the cell wall by providing resistance 36 . Overexpression of chitinase in transgenic rice contributed to increased fungal resistance 37 .…”
Section: Discussionmentioning
confidence: 99%
“…A set of time-scale transcriptome analysis revealed that functional ETI (effector triggered immunity) responses rely on an appropriate time point for transcriptional reprogramming, which is mediated by jasmonate, ethylene, salicylic acid, and PAD4 signaling (19). Transcriptome analysis provided useful information for understanding the resistance mechanism of Brassica napus to clubroot disease (20) and was performed to investigate the regulatory mechanism of Pi9 and Pi21, two R (resistance genes) that control blast fungus (21,22).…”
mentioning
confidence: 99%